2021
DOI: 10.1186/s41983-021-00379-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurological sequelae of COVID-19: a review

Abstract: Background The COVID-19 pandemic has produced a myriad of challenges, including identifying and treating neurological sequelae. Main body COVID-19 can cause olfactory and respiratory dysfunction with average recovery within 1 month and a minority of patients experiencing symptoms at 8-month follow-up. Headaches are also very common (up to 93%) amongst patients with persistent COVID-19 symptoms. COVID-19 illness may also affect cognition, although r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 114 publications
0
23
0
5
Order By: Relevance
“…Symptoms of mental illnesses such as depression, anxiety, obsessive-compulsive, suicidal, neurological, cognitive, and other disorders have increased overall during the COVID-19 pandemic, as clinical, financial, and psychological stress continues. [30][31][32] Our study described the depression, anxiety, and fears observed in HCWs during the waves of COVID-19.…”
Section: Discussionmentioning
confidence: 95%
“…Symptoms of mental illnesses such as depression, anxiety, obsessive-compulsive, suicidal, neurological, cognitive, and other disorders have increased overall during the COVID-19 pandemic, as clinical, financial, and psychological stress continues. [30][31][32] Our study described the depression, anxiety, and fears observed in HCWs during the waves of COVID-19.…”
Section: Discussionmentioning
confidence: 95%
“…Neurological and psychiatric sequelae of COVID-19 are actively being studied. A recent review summarized COVID-19 neurological sequela, ranging from olfactory and gustatory dysfunction and other cranial nerve impairments, headaches, cognitive, memory, and sleep changes, fatigue, akinetic mutism, stroke, worsening of dementia, and Gillian-Barre syndrome [ 62 ]. Anxiety, depression, posttraumatic stress disorder (PTSD), somatization, OCD, and suicide were associated with psychiatric effects during the pandemic [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the significant respiratory complaints of COVID-19, there has been an increasing number of reported neurological complications of the disease. [37][38][39][40] A nationwide retrospective observational study in Italy showed 72.1% of the 646 patients surveyed reported neurological symptoms during their COVID-19 infection.…”
Section: Covid-19 and Its Neurological Manifestationsmentioning
confidence: 99%